Effectiveness of Learning Management System and Peer Assessment Method in Parasitology Learning at Padjadjaran University, Faculty of Medicine - Afiat Berbudi; Faqih Achmad Rabbani; Kurnia Wahyudi (Studies in Learning and Teaching, 2024)
The early 2020 COVID-19 pandemic disrupted community activities, including education. Online education and various teaching methods have been implemented by the Indonesian government to reduce classroom learning. This study investigates the impact of asynchronous learning and peer assessment in the parasitology course via the Learning Management System (LMS). This quantitative study evaluated the effectiveness of Learning Management System to facilitate asynchronous learning and peer assessment in the fifth-semester parasitology course. All 247 course students were the study's target group. The data was acquired using a structured questionnaire. A quantitative analysis was done utilizing Sugiyono's efficacy formula. To draw relevant conclusions, qualitative questionnaire data was recorded and rigorously analyzed. The survey indicated that 37% of respondents thought LMS was beneficial for Parasitology E-learning and 39% said it improved course understanding. In the GIS system, 91% of participants said peer assessment helped them comprehend parasitology topics. This study demonstrates that the LMS can effectively and efficiently facilitate peer assessment to address the challenges in providing feedback to students in order to improve learning outcomes.